Ultra-high field magnetic resonance imaging parameter mapping in the posterior horn of ex vivo human menisci. Issue 3 (March 2019) - Olsson, E.; Folkesson, E.; Peterson, P.; Önnerfjord, P.; Tjörnstrand, J.; Hughes, H.V.; Englund, M.; Svensson, J.
Summary: Objective: To investigate the relationship between meniscus magnetic resonance (MR) relaxation parameters and meniscus degradation through quantitative imaging of ex vivo posterior horns of menisci from subjects with and without knee osteoarthritis (OA). Design: We sampled medial and lateral menisci from ten medial compartment knee OA patients (mean age 63 years) undergoing total knee replacement and from ten deceased donors (references, mean age 51 years). MR relaxation parameters T2*, T2 and T1 of the posterior horn were measured at a 9.4 T scanner. Comparisons were made between OA patients and references (with adjustment for age) as well as between medial and lateral menisci from the same knees. Results: Mean values (standard deviation) of mean T2* were 13 (3.8), 6.9 (2.3), 7.2 (1.9) and 7.2 (1.7) ms for the medial and lateral patient menisci and the medial and lateral reference menisci, respectively. Corresponding values were 17 (3.7), 9.0 (2.2), 12 (4) and 9.0 (1.3) ms for T2 and 1810 (150), 1630 (30), 1580 (90) and 1560 (50) ms for T1. All three relaxation times were significantly longer in medial OA menisci compared to the other groups. Among medial reference menisci, relaxation times (mainly T1) tended to increase with age. Conclusions: MR relaxation times T2*, T2 and T1 in the posterior horn are longer in the medial menisci of patients with end-stage medial compartment knee OA compared to the corresponding lateral menisci and to reference menisci. The meniscus seems to undergo intrasubstance alterations related to both OA and ageing.